Creative Families Gender and Technologies of Everyday Life - Mikats, Jana; Kink-Hampersberger, Susanne; Oates-Indruchová, Libora (Palgrave Studies in Mediating Kinship, Representation, and Difference, 2021)
X, 220 p. 2 illus., 1 illus. in color.